A Pharmacokinetic Drug Interaction Between Fimasartan and Linagliptin in Healthy Volunteers - Kang WY; Lee HW; Gwon MR; Cho S; Shim WS; Lee KT; Yang DH; Seong SJ; Yoon YR (Dove Medical Press, 2020)
Woo Youl Kang,1,2,* Hae Won Lee,1,2,* Mi-Ri Gwon,1,2 Seungil Cho,1,2 Wang-Seob Shim,3 Kyung-Tae Lee,3 Dong Heon Yang,4 Sook Jin Seong,1,2 Young-Ran Yoon1,2 1Department of Molecular Medicine, School of Medicine, Kyungpook National University, Daegu, Republic of Korea; 2Department of Clinical Pharmacology, Kyungpook National University Hospital, Daegu, Republic of Korea; 3Kyung Hee Drug Analysis Center, Kyung Hee University, Seoul, Republic of Korea; 4Division of Cardiology, Department of Internal Medicine, School of Medicine, Kyungpook National University, Daegu 41944, Republic of Korea*These authors contributed equally to this workCorrespondence: Young-Ran YoonDepartment of Molecular Medicine, School of Medicine, Kyungpook National University, Daegu, Republic of KoreaTel +82-53-420-4950Fax +82-53-420-5218Email yry@knu.ac.krSook Jin SeongDepartment of Clinical Pharmacology, Kyungpook National University Hospital, Daegu, Republic of KoreaTel +82-53-200-6351Fax +82-53-420-5218Email wintersj@knu.ac.krObjective: Fimasartan, an angiotensin II type 1 receptor blocker, and linagliptin, a dipeptidyl-peptidase-4 inhibitor, are frequently coadministered to treat patients with hypertension and diabetes, respectively. This study sought to evaluate the pharmacokinetic interactions between fimasartan and linagliptin after co-administration in healthy Korean subjects.Methods: The overall study was divided into two separate parts, with each part designed as an open-label, multiple-dose, two-period, and single-sequence study. In Part A, to investigate the effect of linagliptin on fimasartan, 25 subjects received 120 mg fimasartan alone once daily for seven days during Period I, and 120 mg fimasartan with 20 mg linagliptin for seven days during Period II. In Part B, to examine the effect of fimasartan on linagliptin, 12 subjects received only linagliptin once daily for seven days during Period I, followed by concomitant administration of fimasartan for seven days during Period II, at the same doses used in Part A. Serial blood samples were collected at scheduled intervals for up to 24 h after the last dose to determine the steady-state pharmacokinetics of both drugs.Results: Thirty-six subjects completed the study. The geometric mean ratio and 90% confidence intervals for maximum plasma concentration at steady state (Cmax,ss) and area under the concentration–time curve at steady state (AUCτ,ss) of fimasartan with or without linagliptin were 1.2633 (0.9175– 1.7396) and 1.1740 (1.0499– 1.3126), respectively. The corresponding values for Cmax,ss and AUCτ,ss of linagliptin with or without fimasartan were 0.9804 (0.8480– 1.1336) and 0.9950 (0.9322– 1.0619), respectively. A total of eight adverse events (AEs) were reported and the incidence of AEs did not increase significantly with co-administration of the drugs.Conclusion: Our results suggest that there are no clinically significant pharmacokinetic interactions between fimasartan and linagliptin when co-administered. Treatments were well tolerated during the study, with no serious adverse effects.Clinical Trial Registry: http://clinicaltrials.gov, NCT03250052.Keywords: fimasartan, pharmacokinetics, drug–drug interaction, linagliptin, safety